Pengaruh Daya Tarik Wisata, Media Sosial, dan Nilai Terhadap Minat Berkunjung Ke Desa Wisata Air Terjun Cunca Wulang Kabupaten Manggarai Barat - Sumiati, Sumiati; Rinaldi Tanjung (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research aims to determine the influence of tourist attractions, social media, and values on the interest in visiting the Cunca Wulang waterfall tourist village in West Manggarai Regency. This research uses a quantitative research method. The population in this study consists of all tourists who have ever visited the Cunca Wulang Waterfall Tourism Village in West Manggarai Regency. The sample in this study consists of 100 respondents. The sampling technique used in this study is purposive sampling, a sampling method based on the researcher's considerations, which is then processed using SPSS. The data collection technique in this study uses a questionnaire. The instrument testing technique in this study uses validity and reliability. And the data analysis technique in this research uses descriptive analysis, classical assumptions, multiple linear regression, coefficient of determination, and hypothesis testing. The results of this study are as follows. Based on the F-test results, an F value of 125.691 was obtained with a significance level of 0.000. This significance value is smaller than the 0.05 significance level, so it can be concluded that the regression model used in this study is statistically significant. In other words, simultaneously, the independent variables consisting of Value, Tourist Attraction, and Social Media significantly influence the dependent variable, which is the Interest in Visiting the Cunca Wulang Waterfall Tourism Village in Manggarai Barat Regency